2018
DOI: 10.1007/s11695-018-3124-0
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Eating Behaviors Predict Outcomes After Bariatric Surgery

Abstract: Patients who endorsed higher levels of pre-surgical emotional eating and food addiction symptoms had poorer weight loss 1 year post-surgery. Providers should consider screening patients for these behaviors during the pre-surgical psychosocial evaluation which would allow opportunities for psychotherapy and potential improvement in weight loss outcomes. Future research should examine which interventions are successful at improving problematic eating behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…Follow-up studies after bariatric surgery commonly show a high rate of missing cases [36,43]. Nonparticipants analyses from large epidemiological studies suggests that responders in general are healthier than non-responders [44], as could be the case in our study.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Follow-up studies after bariatric surgery commonly show a high rate of missing cases [36,43]. Nonparticipants analyses from large epidemiological studies suggests that responders in general are healthier than non-responders [44], as could be the case in our study.…”
Section: Discussionsupporting
confidence: 69%
“…HADS is a commonly used screening instrument for anxiety and depression also for patients undergoing bariatric surgery [36]. The instrument has 14 items on a four-point scale ranging from 0 (nothing) to 3 (very much), yielding anxiety and depression subscores (each ranging from 0-21), and a total score (range 0-42).…”
Section: Questionnairesmentioning
confidence: 99%
“…With regard to therapy response , based on the literature, it has been observed that higher FA, according to YFAS scoring, has been associated with poorer treatment outcome in the case of eating disorders, specifically in Bulimia nervosa (Hilker et al, ), and also in Bariatric Surgery obese patients, where those with FA experienced more difficulties reducing weight prior to the BS (Guerrero Pérez, et al, ) and post‐operatively (Miller‐Matero et al, ).…”
mentioning
confidence: 99%
“…People with obesity report more EE than normal‐weight individuals, 8,9 and especially more EE that is triggered by negative emotions 10 . Patients with obesity who present high levels of EE tend to lose less weight than others after participating in weight management programs 4,11,12 and after undergoing bariatric surgery 13,14 . To improve obesity care and prevention, the risk factors for EE in obesity need to be better identified and understood.…”
Section: Introductionmentioning
confidence: 99%